Optimization of Guidance and Counseling by Bhabinkamtibmas of Polresta Surakarta in Preventing Fraudulent Crimes Utilizing Technology - Patika, Rayhan Anugerah Enggar (Advances in Police Science Research Journal, 2024)
The development of technology has led to an increase in criminal activities, especially fraud. As a state institution tasked with maintaining public security, the Indonesian National Police (Polri) has a responsibility to address this issue. One of the measures taken by Polri to prevent fraud is through the activities of Bhabinkamtibmas, which includes guidance and counselling sessions known as Bimluh. This research aims to investigate why the guidance and counselling activities conducted by Bhabinkamtibmas in Polresta Surakarta, which utilize technology, are not optimal in preventing fraud. Specifically, this study explores the implementation of Bimluh by Bhabinkamtibmas in Polresta Surakarta in preventing fraud through the use of technology and the performance of Bhabinkamtibmas in preventing fraud through guidance and counselling sessions that utilize technology. The theoretical frameworks used in this study are Management, Performance, SWOT, Optimization, Bhabinkamtibmas, Guidance and Counselling, Fraud, Technological Utilization, and Polri Presisi. A qualitative field research approach was employed, with data collection techniques including interviews, observations, and document analysis. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The study concludes that the implementation of Bimluh by Bhabinkamtibmas is still suboptimal, based on the theoretical frameworks employed in this study.